Getting to know the other during school intercultural exchanges - experiences of young people from polish-czech borderland in Cieszyn Silesia - Khojnacjka-Synashko Barbara (Borys Grinchenko Kyiv Metropolitan University, 2017)
Living in a multicultural environment helps a person to take advantage of their potential. Different situations require adaptation and demand constant learning. The incentives to learn can also be social problems, which arise from the lack of understanding of differences and tendency to the emancipation of minority groups who want to maintain their own identity. Education, which provides opportunities for contact with other cultures, helps to identify these problems. It is about intentional intercultural educational situations, is meeting others, learning through experience - in the form of a visit, the participation of students in youth exchanges. The text indicates the essence of intercultural youth meetings - deepening knowledge of ourselves and our culture, making contact with others, interacting and discovering diversity, and dealing with differences. The research was presented concerning the attitude of young people to participate in school intercultural exchanges and their opinions on the benefits that they have brought / can bring to such meetings. The study was carried out in the school year 2014/2015 among young people from the Polish-Czech border area in Cieszyn Silesia.